THE CONCEPT OF INTERACTION BETWEEN THE UNIVERSITIES AND ENTERPRISES IN THE ORGANIZATION OF DUAL TRAINING - O. Petrina; T. Mezentseva (Вестник университета, 2017)
The dual training - a new concept for vocational education, which suggests that the training is carried out simultaneously based on educational institution and enterprise. The article analyzes the problems and prospects of implementation of the dual system based on social partnership of universities and enterprises of light industry.